Peningkatan Pemahaman Konsep Sel Melalui Project Based learning dengan Projek Mikroplas Pada Siswa Kelas VII - Nurhayati Nurhayati; Budi Lenggono (Lembaga Bale Literasi, 2026)
This study was motivated by the low understanding of seventh-grade students regarding the topic of cells. The abstract and microscopic nature of cell concepts often makes them difficult to visualize, resulting in learning that tends to rely on memorization. This research is a classroom action research aimed at improving the learning outcomes of 32 seventh-grade students at SMPIT Nur Hidayah. The research activities consisted of a pre-cycle, Cycle I, and Cycle II. In the pre-cycle, learning was conducted using lecture and discussion methods; in Cycle I, the Project-Based Learning model was implemented with a microscope project; and in Cycle II, a plastiline project was applied. Data were collected through observation, learning outcome tests, and questionnaires. The collected data were analyzed using quantitative and qualitative descriptive analysis, with success indicators set at an average score of 80, a minimum of 80% classical mastery, and an N-gain categorized at least as medium. The results showed that in the pre-cycle, the average score was 51.91 with 3.13% classical mastery. In Cycle I, the average score increased to 60.09 with 15.63% classical mastery, and in Cycle II it further increased to 84.06 with 93.75% classical mastery. The N-gain from the pre-cycle to Cycle I was 0.22 (low), and from Cycle I to Cycle II was 0.58 (medium). Thus, the success indicators were achieved, and it can be concluded that the classroom action using the Project-Based Learning model with the Mikroplas media successfully improved student learning outcomes